Glycosylated α-Azido Amino Acids: Versatile Intermediates in the Synthesis of Neoglycoconjugates - O’Flaherty, Róisín; Velasco-Torrijos, Trinidad (Synlett, 2018)
A series of glycosylated α-azido amino acids was synthesized as precursors for neoglycoconjugates, a class of important biomolecules for drug discovery, and sensor development. The synthetically challenging 1,2-cis α-galactosylated species described herein were designed as building blocks in the synthesis of analogues of α-galactosyl ceramide, a potent immunomodulator. A benzyl-protected 1,2,3-triazolyl α-galactosyl-l-serine derivative was prepared using copper azide alkyne cycloaddition to showcase the potential of glycosylated α-azido amino acids in neoglycoconjugate design.
Keywords: α-azido amino acid; glycosylation; neoglycoconjugates 1,2,3-triazolyl glycosides; CuAAC reaction